¿Quo vadis University? - Viteri Briones., Telmo (Revista Universidad de Guayaquil, 2010)
Author points out severe University of Ecuador problems: small links with social development area because of limited and insufficient true state policies aiming to support an equitable and fair socioeconomic model, sustainable development, etc. where the educational system and specially the superior college and university learning lead a nation-wide transformation process to spread the skills to succeed. Evidence that the superstructure (the legal-political, in this case) of an alone Social Economic Education system does not change the essence of the model, emphasizing the poor culture/consciousness of respect for the laws by the public and conceptual flaws own legal framework that analyzes/compares to establish regulations not apprehend/categorical perception and mixing characteristics concerning dissimilar epistemological paradigms, as if these were the same character. Sustained curriculum supports the institutionalization of our population diagnosis priority needs in full relationship with the market and the inter-communication/agreements between the state, employers, the University, students and their families, inviting specialists to analize the National Development Plan in order to optimize its guidelines so that no small theoretical generalities would rather grasp on the realities/Ecuador and solve problems.